UNDERSTANDING FOOD SECURITY IN THE CONSTRUCTION OF A SHARIA ECONOMIC SYSTEM - Ulfa Jamilatul Farida; Navirta Ayu (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Inequality is a condition of inequity that results in a wide poverty gap in a country. In the future, challenges will arise due to inequality in wealth and prosperity, including in Indonesia. The Islamic economy is a system built on the principles of Islamic law and emphasises that the state is responsible for meeting the needs and welfare of its people. This paper uses qualitative methods and a retrospective approach to reveal how food issues are addressed in the construction of the Islamic economic system in Indonesia. Sharia-based food security is imbued with the main characteristics of Islamic economics, namely good and halal muamalah (transactions). Therefore, to achieve this, it is important to develop an Indonesian Islamic economic master plan based on the main indicator of economic independence in food self-sufficiency as an effort to realise national food security. Indonesia's Islamic economy is growing rapidly, and ideally, the construction of economic independence in the context of realising sharia-based food security should be a priority in the development of Indonesia's Islamic economic master plan based on the main indicator of economic independence in food self-sufficiency as an effort to realise national food security.